4D Biofabrication: 3D Cell Patterning Using Shape-Changing Films - Stroganov, Vladislav; Pant, Jitendra; Stoychev, Georgi; Janke, Andreas; Jehnichen, Dieter; Fery, Andreas; Handa, Hitesh; Ionov, Leonid (Advanced Functional Materials, 2018)
A novel approach for fabrication of 3D cellular structures using new thermosensitive shape-changing polymer films with photolithographically patterned surface—4D biofabrication is reported. The surface of shape-changing polymer films is patterned to selectively adsorb cells in specific regions. The 2D cell pattern is converted to the 3D cell structure after temperature-induced folding of the polymer films. This approach has a great potential in the field of tissue engineering and bioscaffolds fabrication.
CRIS-Team Scopus Importer:2022-04-14
Keywords: actuators; folding; hydrogels; thermoresponsive polymers